2020
DOI: 10.3389/fcell.2020.00361
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Mechanisms of Cell Polyploidy in Insects

Abstract: Polyploidy cells undergo the endocycle to generate DNA amplification without cell division and have important biological functions in growth, development, reproduction, immune response, nutrient support, and conferring resistance to DNA damage in animals. In this paper, we have specially summarized current research progresses in the regulatory mechanisms of cell polyploidy in insects. First, insect hormones including juvenile hormone and 20-hydroxyecdysone regulate the endocycle of variant cells in diverse ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 96 publications
2
23
0
Order By: Relevance
“…gambiae defined by Raddi et al (Raddi et al, 2020) and the "non-hemocyte" gene set in Drosophila from Tattikota et al (Tattikota et al, 2020) for comparison to our cell clusters, we demonstrate that genes expressed in Cluster closely resemble the profiles of non-hemocyte cell types and likely represents cellular debris (such as fat body or oenocytes) associated with perfusion techniques (Figure 2-figure supplement 2). This is further supported by the high DNA content of Cluster 1 cells identified by our FACS methodology (Figure 1-figure supplement 1), where previous studies in mosquitoes (Dittmann et al, 1989) and other insect species (Ren et al, 2020) have demonstrated that fat body cells display increased levels of cell ploidy. Alternatively, Cluster 1 may also represent cell doublets of mixed cell origins (fat body, granulocytes, or oenocytoids) resulting from errors in our FACS isolation methodology.…”
Section: Characterization Of An Gambiae Immune Cell Clusterssupporting
confidence: 82%
See 1 more Smart Citation
“…gambiae defined by Raddi et al (Raddi et al, 2020) and the "non-hemocyte" gene set in Drosophila from Tattikota et al (Tattikota et al, 2020) for comparison to our cell clusters, we demonstrate that genes expressed in Cluster closely resemble the profiles of non-hemocyte cell types and likely represents cellular debris (such as fat body or oenocytes) associated with perfusion techniques (Figure 2-figure supplement 2). This is further supported by the high DNA content of Cluster 1 cells identified by our FACS methodology (Figure 1-figure supplement 1), where previous studies in mosquitoes (Dittmann et al, 1989) and other insect species (Ren et al, 2020) have demonstrated that fat body cells display increased levels of cell ploidy. Alternatively, Cluster 1 may also represent cell doublets of mixed cell origins (fat body, granulocytes, or oenocytoids) resulting from errors in our FACS isolation methodology.…”
Section: Characterization Of An Gambiae Immune Cell Clusterssupporting
confidence: 82%
“…Moreover, Cluster 8 also expresses high levels of hnt/peb, DnaJ-1, Mlf, klu, and lozenge (Figure 3-figure supplement 4) that are indicative of mature Drosophila crystal cells (Koranteng et al, 2020;Miller et al, 2017;Tattikota et al, 2020;Terriente-Felix et al, 2013), suggesting that Clusters 7 and 8 respectively represent populations of immature and mature oenocytoids similar to comparable populations of crystal cells in Drosophila (Cho et al, 2020;Tattikota et al, 2020). Interestingly, the isolation of these oenocytoid populations predominantly in Gate 1 (Figure 1-figure supplement 1) of our FACS methodology suggest that these cells may be polyploid, which may enhance their ability to rapidly undergo protein synthesis in response to immune challenge as previously proposed (Ren et al, 2020).…”
Section: Further Defining Mosquito Granulocyte and Oenocytoid Sub-populationssupporting
confidence: 72%
“…The larval salivary gland grows primarily by endoreplication, resulting in polyploidy cells through multiple S phase replications without entering mitosis [ 23 , 24 ]. Therefore, we tested whether Tctp and 14-3-3ε are required for proper endoreplication by checking the level of bromodeoxyuridine (BrdU) incorporation.…”
Section: Resultsmentioning
confidence: 99%
“…1C means haploid genome. In insects, polyploidy ranges from 4C to 2 048C, the latter detected in salivary glands in Drosophila (Ren et al, 2020). Polyploidy has been linked to high metabolic or synthetic activity, compensation for lack of nuclear DNA, response to environmental conditions and to relationship between cell volume and DNA content (Barow, 2006).…”
Section: Genome Wide Variationsmentioning
confidence: 99%